2019
DOI: 10.15252/embr.201846022
|View full text |Cite
|
Sign up to set email alerts
|

Gadd45α modulates aversive learning through post‐transcriptional regulation of memory‐related mRNA s

Abstract: Learning is essential for survival and is controlled by complex molecular mechanisms including regulation of newly synthesized mRNA s that are required to modify synaptic functions. Despite the well‐known role of RNA ‐binding proteins ( RBP s) in mRNA functionality, their detailed regulation during memory consolidation is poorly understood. This study focuses on the brain function of the RBP Gadd4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
(108 reference statements)
2
10
0
Order By: Relevance
“…Extended access to cafeteria diet in rats increased the brain electrical stimulation in the lateral hypothalamus, pointing out a deficit in the brain reward function [ 32 ]. Therefore, both our data and previous studies [ 26 , 30 , 32 ] suggest that the development of obesity is coupled with neuronal adaptations in the reward system that drive the overeating in order to alleviate the diminished reward, in which CB1 in dorsal telencephalic neurons occupies a key regulatory function. Supporting these findings, we have recently showed that the lack of CB1 in this neuronal subpopulation did not fully mitigate the development of food addiction but significantly promoted a resilient phenotype [ 33 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Extended access to cafeteria diet in rats increased the brain electrical stimulation in the lateral hypothalamus, pointing out a deficit in the brain reward function [ 32 ]. Therefore, both our data and previous studies [ 26 , 30 , 32 ] suggest that the development of obesity is coupled with neuronal adaptations in the reward system that drive the overeating in order to alleviate the diminished reward, in which CB1 in dorsal telencephalic neurons occupies a key regulatory function. Supporting these findings, we have recently showed that the lack of CB1 in this neuronal subpopulation did not fully mitigate the development of food addiction but significantly promoted a resilient phenotype [ 33 ].…”
Section: Discussionsupporting
confidence: 72%
“…Total RNA was isolated from the olfactory cortex and brain punches. RNA isolation, reverse transcription reaction, and real-time PCR analysis were described previously [ 26 ]. In order to evaluate the rescue of CB1 gene expression after AAV-mediated gene delivery, real-time PCR analysis was carried out with Taqman mouse CB1 primers (Mm00432621_s1), and we also designed a specific pair of primers hydridizing to mouse CB1 and rat CB1 transgene (forward: TTC AAA CTG GGT GGG GTT AC; reverse: GCC TGG TGA CGA TCC TCT TA).…”
Section: Methodsmentioning
confidence: 99%
“…Gadd45a (growth arrest and DNA damage-inducible protein 45 alpha) has been found upregulated in response to Sevoflurane along with the corresponding long noncoding RNA ( 35 ) and also activates the p53 pathway. Gadd45a is implicated in hippocampal memory and potentiation ( 36 ). Composite network analysis implicated Gadd45a, a DNA-damage-inducible gene, in modulating NF-kappa B signaling in Sevoflurane related cognitive damage.…”
Section: Discussionmentioning
confidence: 99%
“…[ 71 ] It stimulates DNA excision repair in vitro and promotes global DNA demethylation. [ 75–77 ] More recently, GADD45a was shown to affect the stability of mRNAs involved in memory and synaptic plasticity [ 78 ] in the hippocampus. RNA binding activity of GADD45a is essential for this regulation.…”
Section: Gadd45a Mrna Is Regulated At the Level Of Mrna Synthesis Translation And Decaymentioning
confidence: 99%